The research of the amount of heavy metals and nitroso compounds in concеntrated tomato products - Shutyuk, Vitaliy; Vasylenko, Sergei; Bessarab, Alexander; Benderska (Dushchak), Olga (My University, 2016)
The constant selling race results in need for improving the quality of nutrition products among in-house food and pharmaceutical processing industries, which is an all-important key to success on the consumer market. This requires constant improvement of the product producing technologies. The topical problem of quality is the presence of heavy metals and nitroso compounds in the products. The topical problem of quality is the presence of heavy metals and nitroso compounds in the products. The research aimed at studying the changes in the heavy metal concentration levels (including Zn, Cu, Pb) in tomato products at their thickening has been conducted at the national University of Food Technologies.
Keywords: дослідження; нітрати; томатопродукти; исследование; нитраты; томатопродукты; study; nitrates; tomato; кафедра технології консервування; кафедра теплоенергетики та холодильної техніки